2015
DOI: 10.1111/ijfs.13001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted diffusion of sodium salt replacer and effect on physicochemical properties of pork meat

Abstract: Summary In an attempt to reduce the high intake of dietary salt, the processed meat industry is continuously looking for alternative solutions for salt replacement. The objective of this study was to investigate the effect of employing sonication on the diffusion of sodium salt (NaCl) and a salt replacer (SR) into pork meat. Ultrasound‐assisted brining experiments were carried out using 5% NaCl or SR at power levels of 9.0 and 54.9 W cm−2 for 120 min. Samples were assessed for cooking loss, water mobility, def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…The rate of NaCl diffusion in pork tissue increased with increasing temperature and power ultrasound intensity. Ojha et al (2016) reported that ultrasonic treatment had a low influence on the mass transfer of salt into pork samples at low ultrasonic power. These different results may be due to different ultrasonic power, treatment time, animal species and muscle types.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of NaCl diffusion in pork tissue increased with increasing temperature and power ultrasound intensity. Ojha et al (2016) reported that ultrasonic treatment had a low influence on the mass transfer of salt into pork samples at low ultrasonic power. These different results may be due to different ultrasonic power, treatment time, animal species and muscle types.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ultrasound may also cause possible negative effects, namely lipid and protein oxidation (Kang, Zou, et al, 2016). In recent years, it has also shown that ultrasound can accelerate the mass transfer of meat through cavitation effect (Inguglia, Zhang, Burgess, Kerry, & Tiwari, 2018;Ojha, Keenan, Bright, Kerry, & Tiwari, 2016;Raso, Mañas, Pagán, & Sala, 1999). Siró et al (2009) investigated the effect of low intensity ultrasound (2-4 W/cm 2 ) on diffusion of sodium chloride in porcine tissue during the treatment time (30, 90, and 180 min).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tenderization can be further improved through marination and aging. Because ultrasonic treatment has the added advantage of not causing negative effects to meat products, such as drastic changes in the quality (color, texture, cooked loss, and juiciness), sensory characteristics, and oxidation stability, or causing microbial contamination [55,56], it is a novel approach that is believed to be promising. …”
Section: Shear Force and Tenderness Of Pork Loin On Ultrasound And Agmentioning
confidence: 99%